Numerical study of combustion for a 4-stroke gasoline engine using turbulent flame speed closure model - Mohd Fadzil, Abdul Rahim (2009)
his thesis deals with the numerical study of turbulent premixed combustion of 4-stroke spark ignition (SI) engine using Turbulence Flame Speed Closure (TFSC) model developed by Zimont. The key objective of the modelling is to asses the applicability of TFSC model for SI engine combustion. The study was also conducted with purpose to assess the influential factors that affect the TFSC model’s prediction. The assessment is primarily based on cylinder pressure data and supported by mass fraction burned, visualization of flame propagation, and turbulent flame speed. Recent progress of TFSC modelling demonstrates that the model tends to diverge at high turbulence which associated with high engine speed. This study consists of experimental engine testing to gather experimental data as means of validation and inputs to the numerical engine model and computational fluid dynamic (CFD) modelling of SI combustion on the baseline engine design. Consecutive tests on Mitsubishi Magma 4G15 engine has been carried out at wide-open throttle from 1500 to 4000 revolution per minute (rpm) of engine speed. Where as the condition at wide-open throttle of 2000 rpm is selected as a baseline condition for the initial simulation purpose. The engine model is tested for combustion simulation using the Zimont combustion model coupled with ε − k turbulence model with standard wall function, and the ignition model developed by Lipatnikov. Preliminary results indicate that the model prediction of peak cylinder pressure was strongly dependent on number of iteration per time step. Thus, iteration number has been studied further in order to reveal the crucial modelling factor. Five different cases have been run using 20, 100, 500, 1000 and 1500 number of iterations per time steps. The acquired results show that the acceptable peak cylinder pressure are obtained when the numerical model’s iteration are larger than 1000. The best prediction has been obtained by using 1500 iteration per time step. A large discrepancy is noticed due to the consideration of mixture properties. This clearly an evidence of the importance of appropriate iteration number for transient engine combustion modelling. Further simulation at high engine speed up to 4000 rpm is recommended to be tested in the next stage of the study